A universal incision for robot-assisted thoracic surgery - Jiao, Jia; Guo, Jinbao; Zhao, Jia; Li, Xiangnan; Du, Ming (Frontiers in Surgery, 2022)
Objective This paper aimed to design and explore the versatility of robot-assisted in thoracic surgery incision.Methods The concept of universal incision was designed and put forward. The clinical data of 342 cases of robot-assisted thoracic surgery were summarized, including gender, age, clinical diagnosis, operative method, operative time, conversion to thoracotomy, intraoperative blood loss, number of lymph node dissection, postoperative pathology and stage, postoperative hospital stay, and postoperative complications of the patients.Results The 342 cases of robot-assisted surgery contained 78 cases of pulmonary surgery (including 54 cases of pulmonary lobectomy, 18 cases of segmental pulmonary resection, 6 cases of pulmonary wedge resection), 82 cases of esophageal surgery (including 77 cases of Mckeown approach, 5 cases of esophageal leiomyoma resection), 42 cases of mediastinal tumor (including 32 cases of anterior mediastinal tumor, 10 cases of posterior mediastinal tumor). Among them, 2 cases were converted to thoracotomy (both esophageal cases), and the rest were successful with no massive intraoperative bleeding and no perioperative death.Conclusion The universal incision of robot-assisted thoracic surgery is safe and feasible, and is suitable for most cases of thoracic surgery.